DAMPAK PEMINDAIAN IBU KOTA TERHADAP POTENSI PARIWISATA DI KALIMANTAN TIMUR - Dananjaya, Ahmad Ghazy (Politeknik Pariwisata Medan, 2025)
This study critically examines the profound implications of Indonesia's capital city relocation to Ibu Kota Nusantara (IKN) in East Kalimantan, particularly its multifaceted impact on regional tourism. While the official narrative frames IKN as a catalyst for